2018
DOI: 10.3390/nu10081015
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Manifestations of Celiac Disease: Early Detection for Better Long-Term Outcomes

Abstract: Population-based screening studies have shown celiac disease to be one of the most common chronic gastrointestinal diseases. Nevertheless, because of the diverse clinical presentation, the great majority of patients remain unrecognized. Particularly difficult to identify are the multifaceted extraintestinal symptoms that may appear at variable ages. Although the pathogenesis and long-term outcome of these manifestations are still poorly established, there is some evidence that unrecognized celiac disease predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 98 publications
(131 reference statements)
2
99
0
14
Order By: Relevance
“…In our study, we found the EIM prevalence in 87% of adult celiac patients. CD is frequently reported to be accompanied by bone, joint, liver, skin involvement and anemia (23). Osteoporosis is one of the most common EIM in adult celiac patients, especially in elderly patients and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found the EIM prevalence in 87% of adult celiac patients. CD is frequently reported to be accompanied by bone, joint, liver, skin involvement and anemia (23). Osteoporosis is one of the most common EIM in adult celiac patients, especially in elderly patients and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Since even identical twins with CD may have completely different phenotypes, the balance between genetic and environmental factors is considered to be important. At least partially different pathogenic background of variable presentations of CD is supported by the unique appearance of serological markers in some of these cases (23). Also delayed in diagnosis of CD it was stated that as a result of the increase in gluten exposure, the rate of EIM increased and some findings regressed after diet compliance (2,32).…”
Section: Discussionmentioning
confidence: 99%
“…Cøliaki er en glutenindusert, systemisk, autoimmun sykdom (20,21). Sykdommen blir diagnostisert både hos barn og voksne (20,22).…”
Section: Diskusjonunclassified
“…Sykdommen blir diagnostisert både hos barn og voksne (20,22). Det er i senere tid rettet større oppmerksomhet mot ikke-gastrointestinale symptomer og assosierte lidelser ved cøliaki (21). Studier viser at ekstra-intestinale manifestasjoner er meget vanlig (21,22), inkludert symptomer som kan ligne revmatiske sykdommer (21).…”
Section: Diskusjonunclassified
See 1 more Smart Citation